2018
DOI: 10.1105/tpc.18.00189
|View full text |Cite
|
Sign up to set email alerts
|

MCD1 Associates with FtsZ Filaments via the Membrane-Tethering Protein ARC6 to Guide Chloroplast Division

Abstract: Chloroplasts replicate by binary fission, a process driven by ring-like dynamic division machinery at mid-chloroplast. In , the first molecular assembly of this machinery, the Z-ring, forms via the association of FtsZ1 and FtsZ2 heteropolymers with the inner envelope membrane through the membrane-tethering protein ACCUMULATION AND REPLICATION OF CHLOROPLASTS6 (ARC6). Spatial control of Z-ring assembly ensures the correct placement of the division machinery and, therefore, symmetric chloroplast division. The pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
18
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 58 publications
5
18
0
Order By: Relevance
“…Among the known mid-plastid-localizing proteins, DRP5B (ARC5) and PDV1 clearly show a discontinuous, "array-of-dot"-like localization pattern surrounding the division site, as revealed by GFP tagging (for DRP5B and PDV1) and immunofluorescence microcopy (for DRP5B) (Miyagishima et al, 2006;Okazaki et al, 2009;Miyagishima et al, 2011). Components of the chloroplast division site-determining Min system, including AtMinD1, AtMinE1, and MCD1 (Osteryoung and Pyke, 2014), also appear to exhibit a punctate pattern, as revealed by immunofluorescence microcopy (Nakanishi et al, 2009;Fujiwara et al, 2009a;Miyagishima et al, 2011;Chen et al, 2018b). Nevertheless, the observed punctate signals of AtMinD1, AtMinE1, and MCD1 were generally smaller, more varied in size, and more irregularly aligned along the division plane than those of DRP5B and PDV1 (e.g., Figure 4.3 in Miyagishima et al, 2011).…”
Section: Dynamics Of Parc6 At the Plastid Division Sitementioning
confidence: 95%
“…Among the known mid-plastid-localizing proteins, DRP5B (ARC5) and PDV1 clearly show a discontinuous, "array-of-dot"-like localization pattern surrounding the division site, as revealed by GFP tagging (for DRP5B and PDV1) and immunofluorescence microcopy (for DRP5B) (Miyagishima et al, 2006;Okazaki et al, 2009;Miyagishima et al, 2011). Components of the chloroplast division site-determining Min system, including AtMinD1, AtMinE1, and MCD1 (Osteryoung and Pyke, 2014), also appear to exhibit a punctate pattern, as revealed by immunofluorescence microcopy (Nakanishi et al, 2009;Fujiwara et al, 2009a;Miyagishima et al, 2011;Chen et al, 2018b). Nevertheless, the observed punctate signals of AtMinD1, AtMinE1, and MCD1 were generally smaller, more varied in size, and more irregularly aligned along the division plane than those of DRP5B and PDV1 (e.g., Figure 4.3 in Miyagishima et al, 2011).…”
Section: Dynamics Of Parc6 At the Plastid Division Sitementioning
confidence: 95%
“…The Z ring is confined to the mid-chloroplast, and the formation of the Z ring requires the chloroplast Min system, which includes ARC3, MinD1, and MinE1 9 , 24 , 27 , 29 – 32 . Multiple chloroplast division site 1 (MCD1) is another plant-specific protein that is required for Z ring positioning 33 , 34 . It was previously shown that MCD1 interacted with ARC6 in the stroma and interacted with FtsZ2 in an ARC6-dependent manner 33 .…”
Section: Introductionmentioning
confidence: 99%
“…Multiple chloroplast division site 1 (MCD1) is another plant-specific protein that is required for Z ring positioning 33 , 34 . It was previously shown that MCD1 interacted with ARC6 in the stroma and interacted with FtsZ2 in an ARC6-dependent manner 33 .…”
Section: Introductionmentioning
confidence: 99%
“…In chloroplasts, the Z-ring is formed by the association of FtsZ1 and FtsZ2 heteropolymers on the stromal side of the inner envelope at the division plane via the membrane tethering protein ARC6, a bitopic inner transmembrane protein that stabilizes the plastid FtsZ ring and coordinates the internal and external division machineries ( Vitha et al, 2003 ). There are currently two known stroma-division proteins reported to interact with ARC6: FtsZ2 ( Lohse et al, 2006 ) and MCD1 ( Chen L. et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%